One-Pot Expeditious Synthesis of Pyrazoloindolones via Base-Promoted Electrocyclization, C–N Coupling and Intramolecular Oxidative Cyclization - Korawat, Harshita Singh; Saini, Manoj Kumar; Prajapati, Karmdeo; Singh, Maya Shankar; Basak, Ashok Kumar (Synlett, 2024)
Pyrazoloindolones are synthesized from N-tosylhydrazones in a one-pot multistep process which include base-promoted (i) electrocyclization reaction of N-tosylhydrazones derived from α,β-unsaturated aldehydes, (ii) aromatic nucleophilic substitution, and (iii) a domino cyclization–oxidation process under aerobic conditions.
Keywords: N-tosylhydrazone; electrocyclization; aromatic nucleophilic substitution; oxidative cyclization; pyrazoloindolones